2010
DOI: 10.1080/17415977.2010.498912
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-based damage detection in porous materials

Abstract: We report here on the use of the heat equation to simulate a thermal interrogation method for detecting damage in a heterogeneous porous material. We first use probability schemes to randomly generate pores in a sample material; then we simulate flash heating of the compartment along one of its boundaries. Temperature data along the source and back boundaries are recorded and then analyzed to distinguish differences between the undamaged and damaged materials. These results suggest that it is possible to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 16 publications
(9 reference statements)
0
23
0
Order By: Relevance
“…We first recall the system (1) which corresponds to the physical flash-heat experiment described in [1]. This experiment assumes that the temperature of the specimen is within the solid state phase and the boundaries are perfectly insulated [13].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…We first recall the system (1) which corresponds to the physical flash-heat experiment described in [1]. This experiment assumes that the temperature of the specimen is within the solid state phase and the boundaries are perfectly insulated [13].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…This porosity causes a certain amount of noise in the interrogation signal of any NDE technique. In [1], where we investigated using active thermography to detect damage in porous domains, we found that we could detect damage of a certain size within a porous medium using thermal interrogation. However, the methods developed in [1] were too computationally intensive to use in the sophisticated 54 H. T. BANKS, D. CIORANESCU, A. K. CRINER, AND W. P. WINFREE parameter estimation routines needed to characterize damage.…”
Section: Introduction Nondestructive Evaluation (Nde)mentioning
confidence: 99%
See 3 more Smart Citations